Statistical Design of Biocarbon Reinforced Sustainable Composites from Blends of Polyphthalamide (PPA) and Polyamide 4,10 (PA410) - Mateo Gonzalez de Gortari; Manjusri Misra; Stefano Gregori; Amar K. Mohanty (Molecules, 2021)
A full factorial design with four factors (the ratio of polyphthalamide (PPA) and polyamide 4,10 (PA410) in the polymer matrix, content percent of biocarbon (BioC), the temperature at which it was pyrolyzed and the presence of a chain extender (CE)), each factor with two levels (high and low), was carried out to optimize the mechanical properties of the resulting composites. After applying a linear model, changes in tensile strength, elongation at break and impact energy were not statistically significant within the considered material space, while the ones in the flexural modulus, the tensile modulus, density and heat deflection temperature (HDT) were. The two most influential factors were the content of BioC and its pyrolysis temperature, followed by the content of PPA. The affinity of PPA with a high-temperature biocarbon and the affinity of PA410 with a lower-temperature biocarbon, appear to explain the mechanical properties of the resulting composites. The study also revealed that the addition of CE hindered the mechanical properties. By maximizing the flexural modulus, tensile modulus and HDT, while minimizing the density, the optimal composite predicted is an 80 [PPA:PA410 (25:75)] wt% polymer composite, with 20 wt% of a BioC, pyrolyzed at a calculated 823 °C.